Effect of 6E Learning by Design on Students’ Problem Solving Skills in Sound Waves - Isnawati; Darmadi, I Wayan; Nurjannah; Miftah (Koordinat Jurnal MIPA, 2025)
This study aims to examine the effect of the 6E Learning by Design model on students’ problem-solving skills in learning sound wave material at MAN 2 Palu City. The research used a quasi-experimental method with a nonequivalent pretest-posttest control group design. The population consisted of all class XI MIPA students. The sample was selected using purposive sampling, with class XI MIPA I (n = 34) as the control class and class XI MIPA J (n = 34) as the experimental class. The instrument used was a problem-solving skills open-ended test. The results showed that the increase in problem-solving skills scores in the experimental class was higher than in the control class, with an N-gain value of 0,685, categorized as moderate. Hypothesis testing was conducted using the Mann-Whitney U test at a significance level of 0,05. Furthermore, the effect size was 1,4 (d ≥ 1.3), indicating a strong effect. These results indicate that the 6E Learning by Design model effectively improves students’ problem-solving skills on sound wave material.